Dry Cleaning dalam Perspektif Fikih Taharah (Studi Komparatif Antara Jumhur dan Abū Ḥanīfah): Dry Cleaning in Fiqh of Taharah Perspective (Comparative Study Between Jumhur and Abū Ḥanīfah) - Asri, Asri; Syandri, Syandri; Nur Azizah Arham (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to find out and understand the differences in opinions of Jumhur and Abū Hanīfah regarding the law of dry cleaning. This research uses a type of library research with a normative, case and comparative approach. The results of the research show that the process of removing impurity without using water according to Jumhur ulama cannot be said to be holy, because of caution if the clothes still have unclean substances that stick to the clothes if they are not rinsed using water, so the dry cleaning method for cleaning uncleanness is not in accordance with the Jumhur school of thought, because it must use water to purify the uncleanness, whereas according to the view of the Ḥanafī school of cleaning uncleanness other than using water, the dry cleaning method is in accordance with the school of thought. Ḥanafī because it has been proven to eliminate the smell, color and taste, it is in accordance with the wishes of the Shari'a. Both opinions use the same istinbat method in making arguments, namely, the Qur'an, hadith and kias, but both differ in interpreting the existing arguments.